European Youth Olympic Festivals and European Young Olympic Ambassadors Programme - Pavlinský, Kamil (Πανεπιστήμιο Πελοποννήσου, 2022)
The purpose of this study is to uncover the current European Young Olympic Ambassadors Programme and its activities. Also to find out how successful was this programme during the European Youth Olympic Festival 2022 in Vuokatti, what could be improved for the next editions and what are the conditions to develop successful European Young Olympic Ambassadors programme in the future. The review of literature is built on quantitative data about the European Youth Olympic Festival, its educational programme – the European Young Olympic Ambassadors and about the international youth sport events in general. We did a questionnaire with all seventeen current ambassadors and alumni and interviewed five of them. Results are divided into three parts – online webinars happening before the EYOF, activities for the athletes happening during the event and whole EYOA programme itself. The thesis aims to provide possible practical ways how to improve the programme for the next editions. In all three parts we provide suggested improvements – for the online webinars, activities and for the EYOA programme itself.
Keywords: Αθλητικές διοργανώσεις; Ολυμπιακές αξίες; Διεθνές Ολυμπιακό Φεστιβάλ Νέων; Διεθνείς αθλητικές εκδηλώσεις για νέους; Sports events; Olympic values; European Youth Olympics Festival; International youth sport events; International youth sport events; Educational programme; Mega events; European Young Olympic Ambassadors; Olympic values